Peningkatan Literasi Akuntansi Digital melalui Workshop Software Accounting dan Pembuatan NPWP Online bagi Siswa MAN 3 Bekasi - Rinaldi Sri Herlambang; Adi Suprayoga; Ririn Uke Saraswati; Marcela Saputri; Roziyahtul Khoirot; Vera Ameilia; Novita Syahputri; Siti Julaeha (Pemberdayaan Masyarakat : Jurnal Aksi Sosial, 2025)
The Society 5.0 era requires younger generations to develop strong digital literacy skills, not only in terms of technical technology use but also in understanding digital business administration and legal compliance. This community service program aims to enhance digital accounting literacy among students at MAN 3 Bekasi through training on accounting software and guidance on online registration of the Taxpayer Identification Number (NPWP). The activity was conducted using several methods, including material delivery, live demonstrations, independent practice, and evaluation using pre-test and post-test assessments. The results show a significant increase in participants’ knowledge, with an average improvement of 89.75% after attending the workshop. Furthermore, evaluation feedback indicates that participants expressed a very positive response toward the activity in terms of relevance, content delivery, and implementation process. Therefore, this program successfully contributed to improving students’ readiness to face digital transformation in the fields of accounting and tax administration